Beispiel Nr: 03
$ \text{Gegeben:}\\\text{Umfang} \qquad U \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{U - 2\cdot a}{ 2}\\ \textbf{Gegeben:} \\ U=65m \qquad a=4m \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{U - 2\cdot a}{ 2} \\ U=65m\\ a=4m\\ b = \frac{65m - 2\cdot 4m}{ 2}\\\\b=28\frac{1}{2}m \\ \small \begin{array}{|l|} \hline a=\\ \hline 4 m \\ \hline 40 dm \\ \hline 400 cm \\ \hline 4\cdot 10^{3} mm \\ \hline 4\cdot 10^{6} \mu m \\ \hline 0,004 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline U=\\ \hline 65 m \\ \hline 650 dm \\ \hline 6,5\cdot 10^{3} cm \\ \hline 6,5\cdot 10^{4} mm \\ \hline 6,5\cdot 10^{7} \mu m \\ \hline 0,065 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 28,5 m \\ \hline 285 dm \\ \hline 2,85\cdot 10^{3} cm \\ \hline 2,85\cdot 10^{4} mm \\ \hline 2,85\cdot 10^{7} \mu m \\ \hline 0,0285 km \\ \hline \end{array}\\$